INSTITUTIONAL INVESTORS, POLITICAL CONNECTION, AND SUSTAINABILITY REPORTING QUALITY: EMPIRICAL EVIDENCE FROM INDONESIA - Elva Nuraina; Noorlailie Soewarno (Universitas PGRI Madiun, 2022)
ABSTRACTThis study aims to show empirical evidence of the role of political connections in the relationship between institutional investors and sustainability reporting. With observational data of 2,425 firm years and data analysis using short-term dynamic panel data regression or GMM. This study results that political relations function as a moderating variable. In a sense, a political connection weakens the relationship between institutional investors and genuine sustainability reporting. These results indicate that although institutional investors push for the quality and consistency of sustainability reporting, political connections avoid quality sustainability reporting. The results of this study provide practical implications that allow regulators to evaluate the rules for presenting sustainability reporting information.ABSTRAKTujuan penelitian ini adalah untuk membuktikan secara empiris mengenai peran Political connection dalam hubungan antara investor institusional dan pelaporan keberlanjutan. Dengan menggunakan data observasional 2.425 tahun perusahaan dan analisis data menggunakan GMM, hasil penelitian ini menunjukkan bahwa political connection berfungsi sebagai pure moderator dalam hubungan antara investor institusional dan pelaporan keberlanjutan. Hubungan politik murni melemahkan hubungan antara investor institusional dan pelaporan keberlanjutan. Hasil ini mengindikasikan bahwa koneksi politik yang lebih besar menyebabkan perusahaan menghindari pelaporan keberlanjutan yang berkualitas meskipun investor institusional mendorong kualitas dan konsistensi pelaporan keberlanjutan. Implikasi praktis penelitain ini memungkinkan regulator untuk mengevaluasi aturan penyajian informasi tentang sustainability reporting.